The Effect of Entrepreneurship Education on University Students’ Entrepreneurial Intention - Reni Dwi Astuti; Nurul Fadhilla Anindya Putri (STAI Hubbulwathan Duri, 2023)
This research was conducted to determine the effect of entrepreneurship education on the entrepreneurial intentions of university students, both directly and through the Theory of Planned Behavior component. The variables in the study include entrepreneurship education, attitudes, perceived behavioral control, subjective norms, and intentions. The research begins with the preparation of a questionnaire to measure all variables. The population consists of Faculty of Economics and Business Ahmad Dahlan University undergraduate students who have taken entrepreneurship courses, with 243 respondents. The method used is multiple linear regression and path analysis. The tests carried out included reliability and validity tests; regression coefficient calculations; and testing the significance of the influence of each variable, both directly and indirectly. The study results showed that entrepreneurship education has a positive and significant direct effect on entrepreneurial intentions and indirectly affects entrepreneurial intentions through perceived behavioral control variables. Thus, the quality of learning needs to be improved so that students' entrepreneurial intentions also increase.